Pemeriksaan Kadar Air Dan Minyak Kulit Sebagai Edukasi Kesehatan Kulit Tropis - Tan, Sukmawati Tansil; Santoso, Alexander Halim; Destra, Edwin; Haryanto, Ines; Alexin, Corry Calista (Gotong Royong, 2025)
Imbalance in skin surface water and oil levels serves as an early indicator of skin barrier disruption, particularly in populations residing in tropical climates. Assessing these parameters can effectively raise public awareness regarding the importance of hydration in maintaining skin integrity. This community activity was conducted among adults at St. Francis of Assisi Church, South Jakarta. Skin hydration and oil levels were measured using a portable digital skin analyzer, followed by group education through visual posters emphasizing the role of adequate fluid intake in supporting skin health. A total of 65 participants were assessed. The mean water content was 44.45%, oil content 21%, and the average hydration index was 49.3. While most participants fell within the neutral range, over one-third exhibited low water or oil levels, indicating a potential risk for impaired skin moisture balance. Skin hydration and sebum levels reflect the homeostatic condition of the skin surface, which is closely linked to systemic fluid adequacy. Education based on individual examination results provides a tangible understanding of the role of hydration in preserving skin barrier function, and may support behavioral change toward better fluid management and skin care. Keywords: Hydration, Oil, Tropical Skin, Health Education, Non-Invasive Screening